Quality of Service Analysis on The Network Lte-Advanced Between Smartfren and Provider Telkomsel on Malioboro Street Yogyakarta - Ahmad Dwi Pranata; Widyasmoro; Yessi Jusman (Journal of Telecommunication Control and Intelligent System, 2021)
LTE-Advanced is one of the communication technologies that can build the global telecommunications industry. As one of the bases for the use of networks that are widely used in the world, the LTE-Advanced network can meet consumer needs. There are several factors that can affect the quality of the network (network quality), one of which is the quality of service. In this study, to measure the quality of service using 3 parameters, namely throughput, latency and jitter. Based on the results that have been carried out using the walk test method and speedtest software for 4 days, the average throughput range value for smartfren providers is 19.8-28.2 Mbps and for Telkomsel providers of 32.5-49.1 Mbps of course. the results from both providers are included in the TIPHON standard excel category because they are in the range >2.1 mbps. In the latency parameter, the average range for both providers is 24.6-28.3 ms on the smartfren provider and 27.9-42.3 ms on the Telkomsel provider if it is included in the TIPHON standard, the results from both providers are in the perfect category because they are at ranges < 150 ms. In the jitter parameter, the average range of results is 8.3-12.7 ms on the smartfren provider while on the Telkomsel provider it is 16-50.9 ms, the average range of the jitter parameters includes index 3 or good because it is in the range 0-75 ms. Based on the results of the measurement of quality of service which consists of 3 parameters, namely throughput, latency and jitter, all of them are included in the appropriate category and are good for use in the Malioboro road area and its surroundings.